2016
DOI: 10.1021/acsphotonics.5b00647
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Chemical Imaging with Plasmonic Substrates

Abstract: We demonstrate super-resolution chemical imaging with plasmonic nanoholes via surface-enhanced Raman spectroscopy (SERS). Due to large field enhancements, blinking behavior of SERS hot spots was observed and processed using a stochastic optical reconstruction microscopy (STORM) algorithm. This enabled localization to within 10 nm and high-resolution imaging. However, illumination of the sample with a static laser beam produced only SERS hot spots in fixed locations, leaving noticeable gaps in the final images.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…By adapting the experimental protocols of super resolution uorescence microscopy, the characteristic stochastic intensity uctuations of SM-SERS have been exploited to construct high resolution images of SMs residing within hot spots. [135][136][137] In this case, the centroid position was obtained by the point spread function to reveal the location of SMs in the hot spot and over the laser spot. 135 This method makes use of the blinking of SM-SERS to avoid overlap between point spread functions from different hot spots.…”
Section: Temporal Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…By adapting the experimental protocols of super resolution uorescence microscopy, the characteristic stochastic intensity uctuations of SM-SERS have been exploited to construct high resolution images of SMs residing within hot spots. [135][136][137] In this case, the centroid position was obtained by the point spread function to reveal the location of SMs in the hot spot and over the laser spot. 135 This method makes use of the blinking of SM-SERS to avoid overlap between point spread functions from different hot spots.…”
Section: Temporal Resolutionmentioning
confidence: 99%
“…A SERS image of collagen ber with 10 nm resolution was demonstrated by employing a plasmonic nanohole array and a laser optical diffuser to simultaneously excite different areas of the sample and thus obtain images without blank spots. 136 Recently, high-speed super resolution SERS imaging was developed by taking advantage of signal uctuations due to surface reconstruction of silver nanoparticles, super-resolution tting, and an Airyscan detector. 138 A point spread function from a single intensity uctuation (SIF) occurring at a single nanoparticle fully-coated with an analyte is imaged by the Airyscan detector on the submillisecond time scale.…”
Section: Temporal Resolutionmentioning
confidence: 99%
“…The plasmonic substrates seeded with bacteria were illuminated with a 660 nm laser (Laser Quantum) covering approximately a 10 µm by 10 µm square. We have shown previously that due to the often random and non-uniform distribution of SERS hotspots, it is possible to “fill in” any gaps by randomly varying the phase of the illumination pattern 53 , 54 into a speckle pattern. This can be accomplished in several ways, including using a simple optical diffuser placed in the beam path 54 .…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that SERS-STORM provides high-fidelity images of biological structures, such as collagen protein fibers 53 , and the light can be band-pass filtered to provide some rudimentary chemical information from the emitted SERS light 54 . However, the technique required a tedious manual tuning process of the band-pass filter and dozens of image acquisitions to provide any spectral information, and the resolution of a compiled SERS spectrum is limited to the band-pass width of the filter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a technique employing stochastic optical reconstruction microscopy (STORM) algorithms was used to process SERS spectra, enabling chemical‐specific, super‐resolution images . The spatial location of SERS “hot‐spots” were dynamically shifted over nanohole arrays or roughened Ag films with subdiffraction‐limited resolution using a spatial light modulator . The dynamically shifted SERS “hot‐spots” generated “blinking” events where SERS spectral information was collected.…”
Section: Bacterial Imaging/mapping With Sersmentioning
confidence: 99%